Development of mangrove paddy fields in Casamance southern Senegal - Barry, Boubacar (2009)
Mangroves areas in Casamance have been traditionally used for rice growing, fishing, fish culture, shell picking and wood. Senegal has been affected by drought since 1963 and this has had an adverse effect on the mangroves leading to a decrease in the total area. Intensification of agriculture and increasing population pressure has resulted in increased erosion and siltation. Given the shortage of rainfall due to recurrent droughts over the last three decades, one can easily observe a tendency towards increased salinity of soils and the underlying water table. Site development has become the only solution to the salt intrusion problem since early 1970s.The present paper focuses on the different types of site development such as the traditional polder and anti-small dams and their role in increasing rice production.